2021
DOI: 10.1128/mbio.00281-21
|View full text |Cite|
|
Sign up to set email alerts
|

COVID-19 Severity Is Associated with Differential Antibody Fc-Mediated Innate Immune Functions

Abstract: Beyond neutralization, antibodies binding to their Fc receptors elicit several innate immune functions including antibody-dependent complement deposition (ADCD), antibody-dependent cell-mediated phagocytosis (ADCP), and antibody-dependent cell-mediated cytotoxicity (ADCC). These functions are beneficial, as they contribute to pathogen clearance; however, they also can induce inflammation. We tested the possibility that qualitative differences in SARS-CoV-2-specific antibody-mediated innate immune functions con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 15 publications
(16 reference statements)
2
64
0
Order By: Relevance
“…Further, we could not evaluate the contribution of the detection platform, instrumentation, or automation of ECLIA, CLIA, or ELISA in addition to the differences in the choice and preparation of recombinant antigen, all of which were used in the analyzed assays. We focused on total antibody and IgG antibody responses in blood and did not evaluate the impact of different immunoglobulin classes or IgG subclasses with respect to microneutralization ( 33 ) or functionality ( 34 ). Exploratory data from our center and the available literature suggest that detection of IgA is too variable and cannot be used reliably in approximately 1% of patients with selective or partial IgA deficiency ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Further, we could not evaluate the contribution of the detection platform, instrumentation, or automation of ECLIA, CLIA, or ELISA in addition to the differences in the choice and preparation of recombinant antigen, all of which were used in the analyzed assays. We focused on total antibody and IgG antibody responses in blood and did not evaluate the impact of different immunoglobulin classes or IgG subclasses with respect to microneutralization ( 33 ) or functionality ( 34 ). Exploratory data from our center and the available literature suggest that detection of IgA is too variable and cannot be used reliably in approximately 1% of patients with selective or partial IgA deficiency ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…To this end, a subset of monoclonal antibodies isolated from SARS-CoV patients that were able to cross-react with, but not neutralize SARS-CoV-2 were able to confer protection in a mouse model 42 . Indeed, both passive transfer experiments of monoclonal antibodies [43][44][45][46][47] and evaluation of polyclonal antibodies raised in the context of vaccination or infection [48][49][50] have shown that effector mechanisms contribute to antiviral activity in vivo. This evidence extends beyond correlative observations 45,48 to include mechanistic 1 evidence of in vivo contributions via Fc sequence engineering to knockout or enhance these activities 44,46 , as well as on the basis of depletion of effector cells 46 .…”
Section: Discussionmentioning
confidence: 99%
“…It is important to understand how these antibodies or antibodies contained in IVIg preparations, interplay between them and thus can modify disease's severity. 47 …”
Section: Immunological Effects Of Ivig In Covid‐19mentioning
confidence: 99%